SURVEI MANAJEMEN SARANA DAN PRASARANA DI STADION JATIDIRI KOTA SEMARANG PADA TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
This study used qualitative methods , as it aims to describe the role of management : planning ( planning) , organizing ( organizing ) , directing ( leading) and monitoring ( controlling) through rationalization of the number of existing facilities and infrastructure . The data was collected through observation, interviews , questionnaires and documentation . Intsrumen availability of data in the form of research facilities and infrastructure . Data analysis in this study includes qualitative data in the form of finding the conditions existing facilities and infrastructure at the stadium Identity Semarang .The results of this study illustrate that the management system in the stadium Identity Semarang already well underway in accordance with the purposes and functions . For existing facilities and infrastructure already includes base so it can be used for matches in the national event .Suggestions that should be noted is the management of the stadium Identity Semarang need for programs that can be targeted , the use of technology for marketing , addition or modification of facilities and infrastructure and the maintenance of facilities and infrastructure need to be developed